The role of immigrant associations in the host society: theoretical questions and empirical evidence - Morell Blanch, Antonio (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The associations, of immigrants or natives, are the result of a human need: the need to meet, to engage in dialogue, to interchange affection, restlessness and experiences. But moreover, in the case of immigrants, at least in a first stage of the migratory process, this need is accentuated by the feeling of isolation and solitude caused by having to face unknown surroundings. In this sense, the importance of the associations of immigrants lies in that they provide security. In spite of it, there isn’t a lack of critical points of view which consider that immigrant associations are an obstade to integration in the new society because they contribute to reproduce their own schemes of the society of origin. The present article displays the results of the fieldwork carried out with the purpose of empirically verifying the hypothesis that immigrant associations often act like catalysts of the process of social integration of the immigrants.